2008
DOI: 10.1002/pen.21007
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic 6FDA‐ODA copolyimide membranes for gas separation and pervaporation: Correlation of separation properties with diamine monomers

Abstract: Copolyimides were synthesized from 4,4 0 -(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 4-aminophenyl ether (ODA) with 4-aminophenyl sulfone (DDS), 4,4 0 -methylenedianiline (MDA), 4,4 0 -bis(3-aminophenoxy)diphenyl sulfone (BADS), 4,4 0 -bis(3-aminophenoxy) benzophenone (BABP), and 2,6-bis(3-aminophenoxyl) benzonitrile (DABN) as the third monomer. Surface free energies and interfacial free energies were calculated for comparison of the membrane hydrophilicity. Gas permeation was carried out with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The other parameters such as residual solvent and membrane or dense/film preparation procedure also influence the polymer structure and hence their permeability coefficients. In some studies, the permeability unit was reported as GPU; in order to convert it to Barrer, GPU was multiplied with the average film thickness [30][31][32]. However, the thickness of the selective layer is not known with high accuracy in case of asymmetric membranes, so this will also bring another source of error.…”
Section: Methodology and Data Usedmentioning
confidence: 99%
“…The other parameters such as residual solvent and membrane or dense/film preparation procedure also influence the polymer structure and hence their permeability coefficients. In some studies, the permeability unit was reported as GPU; in order to convert it to Barrer, GPU was multiplied with the average film thickness [30][31][32]. However, the thickness of the selective layer is not known with high accuracy in case of asymmetric membranes, so this will also bring another source of error.…”
Section: Methodology and Data Usedmentioning
confidence: 99%
“…For pure polymer, absorption bands at 1785, 1718, 1351 and 719 cm -1 corresponded to asymmetric and symmetric C=O stretching, C-N stretching and imide five-ring deformation [25]. Besides, the signal at 1327 cm -1 was related to the asymmetric stretching of SO2 [35]. In the case of pure MOFs, NH2-MIL-53(Al) and NH2-MIL-101(Al) bands at 3504 and 3391 cm -1 and the shoulder at 1624 cm -1 corresponded to the asymmetric and symmetric amine stretching and the N-H scissoring vibration, thus confirming the presence of amino groups in the framework [20,24].…”
Section: Preparation and Characterization Of Mmmsmentioning
confidence: 96%
“…One glassy polymer of interest is polyimide containing 4,4 -(hexafluoroisopropylidene) diphthalic anhydride (6FDA) [8][9][10][11][12][13][14][15][16]. It consists of bulky CF 3 groups that reduce chain packing and increase chain stiffness due to steric hindrance.…”
Section: Introductionmentioning
confidence: 99%